Antidepressant sertraline impairs the induced morphological defense of Ceriodaphnia cornuta in response to Chaoborus larvae kairomone. (November 2020) - Zhu, Shuangshuang; Wu, Guangjin; Gu, Lei; Sun, Yunfei; Zhang, Lu; Huang, Yuan; Lyu, Kai; Yang, Zhou
Abstract: Antidepressants discharged into natural waters are likely to become a new type of endocrine pollutant, which may impact the interspecific relationship in aquatic ecosystem. Induced defense of cladocerans plays an important role in maintaining the balance of interspecific relationships between cladocerans and higher trophic levels. Here we studied the effects of antidepressant sertraline, a selective serotonin reuptake inhibitor, on the induced defensive traits of Ceriodaphnia cornuta in response to invertebrate predator Chaoborus larvae kairomone, including morphological defense and life history traits. We also conducted the predation experiments to check the selection rate of Chaoborus larvae during directly ingesting C. cornuta that were exposed to Chaoborus larvae kairomone at high concentration of sertraline. Results showed sertraline had an interference effect on the induced morphological defense of C. cornuta in response to Chaoborus larvae kairomone, i.e. the high concentration of sertraline (20 and 100 μg L −1 ) significantly reduced the horns induction. However, the different concentrations of sertraline generally did not affect the life history traits of C. cornuta, regardless of presence or absence of Chaoborus larvae kairomone. The predation experiment demonstrated that the inhibition of sertraline on the induced morphological defense of C. cornuta can promote the feeding selective efficiency of Chaoborus larvae, and thus cause C. cornuta easily to be predated by Chaoborus larvae. Our results suggested that sertraline at the concentrations that are not direct harmful to life history traits of C. cornuta can seriously affect the predator-prey relationship, indicating that effects of pollutants on interspecific relationships should be considered comprehensively to avoid underestimating the potential risk of pollutants to ecosystems. Graphical abstract: Image 1 Highlights: Ceriodaphnia formed induced horns in response to Chaoborus larvae kairomone. Sertraline impaired the induced morphological defense of Ceriodaphnia. Sertraline did not affect the life history traits of Ceriodaphnia. Sertraline caused Ceriodaphnia easily to be predated by Chaoborus larvae. Sertraline can be a potential threat to predator-prey relationship. Abstract : Antidepressant caused Ceriodaphnia more susceptible to be predated by Chaoborus larvae through interfering the induced morphological defense of Ceriodaphnia .